Study Protocol: 6th National Survey of Australian Secondary Students and Adolescent Sexual Health, 2018 - Fisher, Christopher; Mikolajczak, Gosia; Ezer, Paulina; Kerr, Lucille; Bellamy, Rosalind; Brown, Graham; Waling, Andrea; Lucke, Jayne (Frontiers in Public Health, 2019)
Introduction: Since 1992 the Australian Government has funded a periodic national survey of HIV and Sexually Transmissible Infection (STI) knowledge and sexual risk behaviour among secondary school students. Adolescents continue to be a priority population in public health efforts to reduce rates of STIs in Australia. The purpose of the survey is to inform progress on national strategic sexual health priorities. The results are used by federal and state/territory government agencies, youth-serving community organisations and health educators to improve knowledge, promote healthy sexual behaviours and target educational efforts aimed at communicating public health messages to young people. Materials and equipment: The 6th survey entitled the “National Survey of Secondary Students and Adolescent Sexual Health” was conducted online in 2018 among 14-18 year olds living in Australia. The anonymous self-complete survey contained up to 286 items assessing three primary domains of knowledge, behaviours and education experiences. Factual knowledge measures covered HIV transmission and STI knowledge around transmission and prevention covering gonorrhoea, Chlamydia, syphilis, hepatitis, herpes and HPV. Behavioural measures examined perceived susceptibility, peer norms, protective behaviours, age of onset for various behaviours, reasons for not being sexually active yet, and/or sexual histories with additional detail on most recent sexual event. The 6th survey was completed by 8,400 Australian adolescents a represents a broad cross-section by age, gender, year in school, type of school (e.g., government, Catholic), and state/territory which closely matched census data on these strata. The one-of-a-kind survey instrument, grounded in public health theories, may prove valuable for public health researchers. Expected impact of the study on public health: Findings from the 6th National Survey of Secondary Students and Adolescent Sexual Health will contribute important insights into current knowledge, behaviours and educational experiences of young people. Results, similar to previous iterations of the survey, will inform public health practitioners, policymakers, educators, and advocates for the sexual health and wellbeing of young Australians. Results may assist sexual health services to align with broader public health goals articulated in the national HIV and STI strategies aimed to reduce the burden of disease and improve the quality of sexual lives of young Australians.